Preventif Tuberkulosis Paru Melalui Edukasi Kesehatan Kepada Masyarakat - Pengemanan, Victory Osvaldo; Tarangi, Filep Marfil (Universitas Madako Tolitoli, 2025)
Tuberculosis remains a health issue not only in Indonesia but also globally. The country needs to strive for the realization of a resilient and Tuberculosis-free Indonesian society through a Tuberculosis elimination program. The aim of this educational activity is to provide Information, Education, and Communication (IEC) related to Pulmonary Tuberculosis to the community at Puskesmas Ch. M Tiahahu in Ambon City. This educational initiative is conducted through lecture-style presentations and the distribution of leaflets to attendees at the health center. The results of the activity indicate that the education provided has generally met the targets outlined in the Program Operational Event (POA). However, the number of participants still does not cover the entire working area of Puskesmas Ch. M. Tiahahu. This is attributed to the fact that the education sessions are conducted before the commencement of services at the health center, limiting the number of participants at that time.